Identifikasi Potensi Ketersediaan Lahan Ruang Terbuka Hijau Publik di Palmerah Jakarta Barat - Nanda Mahrunnisya; Dadan Mukhsin (UPT Publikasi Ilmiah Unisba, 2023)
Abstract. The lack of existing green open spaces, especially public green open spaces, in densely populated urban residential areas will have an impact on the quality of the environment and the city's comfort. The urgency of this research is to examine the existing situation, assess the area-based needs, and explore the potential availability of land for public green open spaces in Palmerah District. The theory used as a reference to identify the potential availability of land for public green open spaces is based on the policy of Minister of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) Regulation Number 14 of 2022 concerning the Provision and Utilization of Green Open Spaces. The research adopts a descriptive qualitative and descriptive quantitative approach with data collection methods including primary data (field observations, documentation) and secondary data (literature review, institutional surveys). The analysis methods used include geospatial analysis for mapping the existing public green open spaces, analysis of the area-based needs for public green open spaces using statistical calculations, and overlaying maps using ArcGIS 10.7. Based on the analysis, it is found that the potentially suitable land for public green open spaces has a total area of 17.5 hectares or approximately 2% of the district's total area. If maximized, the land can increase the existing public green open spaces in Palmerah District to 32.5 hectares or approximately 4% of the district's total area. Abstrak. Kurangnya eksisting ruang terbuka hijau terutama ruang terbuka hijau publik pada kawasan permukiman padat penduduk di perkotaan akan berdampak pada kualitas lingkungan dan kenyamanan kota. Urgensi penelitian ini untuk melihat eksisting, kebutuhan berdasarkan luas wilayah, serta potensi ketersediaan lahan untuk ruang terbuka hijau publik yang berada di Kecamatan Palmerah. Teori yang dijadikan sebagai acuan untuk mengidentifikasi potensi ketersediaan lahan ruang terbuka hijau publik ini berdasarkan kebijakan Peraturan Menteri ATR/KBPN RI Nomor 14 tahun 2022 tentang Penyediaan dan Pemanfaatan Ruang Terbuka Hijau. Metode pendekatan yang dipakai yakni secara deskriptif kualitatif dan deskriptif kuantitatif dengan metode pengumpulan data yakni secara primer (observasi lapangan, dokumentasi) dan sekunder (studi literatur, survey instansional). Metode analisis yang digunakan yakni analisis geospasial untuk pemetaan eksisting ruang terbuka hijau publik, analisis kebutuhan ruang terbuka hijau publik dengan perhitungan statistik, dan overlay peta menggunakan arcgis 10.7. Berdasarkan hasil analisis menghasilkan bahwa lahan yang potensial di untuk dijadikan ruang terbuka hijau publik memiliki luas total sebesar 17,5 Ha atau jika dipersentase yaitu sebesar 2% dari luas wilayah kecamatan. Jika dimaksimalkan maka lahan dapat menambah eksisting ruang terbuka hijau publik yang ada di Kecamatan Palmerah menjadi 32,5 Ha atau bertambah menjadi 4% dari luas wilayah kecamatan.